Respuesta :

Solve the equation

[tex]\\ \sf \longmapsto 4(-x+4)=12[/tex]

[tex]\\ \sf \longmapsto -4x+16=12[/tex]

[tex]\\ \sf \longmapsto -4x=12-16[/tex]

[tex]\\ \sf \longmapsto -4x=-4[/tex]

[tex]\\ \sf \longmapsto x=\dfrac{-4}{-4}[/tex]

[tex]\\ \sf \longmapsto x=1[/tex]

[tex]\large\bf{\orange{ \implies}} \: \tt \: \: 4 \: ( - x \: + \: 4) \: = \: 12[/tex]

[tex]\large\bf{\orange{ \implies}} \: \tt \: \: - 4x \: + \: 16 \: = \: 12[/tex]

[tex]\large\bf{\orange{ \implies}} \: \tt \: \: - 4x \: = \: 12 \: - 16[/tex]

[tex]\large\bf{\orange{ \implies}} \: \tt \: \: - 4x \: = \: - 4[/tex]

[tex]\large\bf{\orange{ \implies}} \: \tt \: \:x \: = \: \frac{ \cancel{- 4} \: \: ^{1} }{ \cancel{- 4}} [/tex]

[tex]\large\bf{\orange{ \implies}} \: \bf \: \:x \: = \: 1[/tex]

[tex]\Large\underbrace{\textrm{{{\color{blue}{Hence , Proved}}}}}[/tex]